Establishing Pharmacy in Nepal: A Practical Guide for Fresh Graduates - Deo, Satish Kumar; Lamichhane, Lekhnath; Adhikari, Rojina (Nepal Journal of Health Sciences, 2024)
Establishing a pharmacy in Nepal presents an exciting yet challenging venture for fresh graduates. The journey involves navigating regulatory hurdles, managing inventory, and building strong supplier relationships. With proper guidance on market dynamics, licensing, and technology adoption, aspiring pharmacists can successfully contribute to the healthcare system while creating a thriving business.